The Second Slavery and World Capitalism: A Perspective for Historical Inquiry - Tomich, Dale (International review of social history, 2018)
The concept of the second slavery radically reinterprets the relation of slavery and capitalism by calling attention to the emergence of extensive new zones of slave commodity production in the US South, Cuba, and Brazil as part of nineteenth-century industrialization and world-economic expansion. This article examines the conceptual framework and methodological procedures that inform this interpretation. It reformulates the concept of the capitalist world-economy by emphasizing the mutual formation and historical interrelation of global–local relations. This open conception of world-economy permits the temporal-spatial specification of the zones of the second slavery. In this way, it is possible both to distinguish the new zones of the second slavery from previous world-economic zones of slave production and to establish the ways in which they are formative of the emerging industrial world division of labor. From this perspective, analysis of sugar production in Jamaica, Guyana, and Cuba discloses spatial-temporal differences between what would otherwise be taken as apparently similar historical-geographical complexes. This comparison demonstrates how world-economic processes produce particular local histories and how such histories structure the world-economy as a whole. This approach locates the crisis of slavery during the nineteenth century in the differentiated response to processes of world accumulation, rather than the incompatibility of slave production with industrialization and open, competitive markets. More generally, it calls attention to the continuity of forms of forced labor in the historical development of the capitalist world-economy and to the ways that processes of capitalist development produce social-economic differentiation and hierarchy on a world scale. Dale Tomich. Le second esclavage et le capitalisme mondial: Une perspective pour la recherche historique. Le concept du second esclavage réinterprète radicalement la relation entre l’esclave et le capitalisme, en attirant l’attention sur l’émergence de nouvelles zones étendues de production de marchandise esclave dans le sud américain, à Cuba et au Brésil en tant que partie de l’industrialisation du dix-neuvième siècle et de l’expansion économique mondiale. Cet article étudie le cadre conceptuel et les procédures méthodologiques qui façonnent cette interprétation. Il reformule le concept de l’économie mondiale capitaliste, en mettant l’accent sur la formation mutuelle et l’interrelation historique des relations globales-locales. Cette conception ouverte de l’économie mondiale permet la spécification temporelle-spatiale des zones du second esclavage. De la sorte, il est possible tant de distinguer les nouvelles zones du second esclavage de zones économiques mondiales antérieures de production d’esclavage que de définir les manières dont elles sont formatives de la division du travail du monde industriel émergeant. Dans cette optique, l’analyse de la production de sucre en Jamaïque, en Guyane et à Cuba révèle des différences spatiales-temporelles entre ce que l’on prendrait sinon pour des complexes historiques-géographiques apparemment semblables. Cette comparaison démontre comment des processus économiques mondiaux suscitent des histoires locales particulières, et comment ces histoires structurent l’économie mondiale dans son ensemble. Cette approche situe la crise de l’esclavage dans la réponse différentiée à des processus d’accumulation mondiale, plutôt que dans l’incompatibilité de la production d’esclaves avec l’industrialisation et des marchés ouverts et concurrentiels. Plus généralement, il attire l’attention sur la continuité de formes de travail forcé dans le développement historique de l’économie mondiale capitaliste, et sur les manières par lesquelles des processus du développement capitaliste produisent une différenciation et une hiérarchie socio-économiques à une échelle mondiale. Traduction: Christine Plard Dale Tomich. Die zweite Sklavenwirtschaft und der Weltkapitalismus: Eine historische Untersuchungsperspektive. Die Vorstellung einer zweiten Sklavenwirtschaft stellt eine radikale Neuinterpretation des Verhältnisses von Sklaverei und Kapitalismus dar. Sie macht auf die Entstehung umfangreicher neuer Gebiete sklavenbasierter Warenproduktion in den US-amerikanischen Südstaaten sowie in Kuba und Brasilien aufmerksam, wie sie im 19. Jahrhundert im Kontext von Industrialisierung und weltwirtschaftlicher Expansion zu verzeichnen war. Der Beitrag untersucht den begrifflichen Rahmen und die methodologischen Verfahren, die mit diesem Ansatz einhergehen, und legt zugleich auch eine Neuinterpretation des Begriffs der kapitalistischen Weltwirtschaft vor, die die wechselseitige Prägung und historische Verschränkung globaler und lokaler Verhältnisse betont. Ein solches offenes Verständnis der Weltwirtschaft erlaubt es, die Zonen der zweiten Sklavenwirtschaft räumlich und zeitlich zu bestimmen. So wird es zum einen möglich, die Zonen der neuen oder zweiten Sklavenwirtschaft von früheren weltwirtschaftlichen Zonen sklavenbasierter Produktion zu unterscheiden. Zum anderen kann herausgearbeitet werden, auf welche Weise die Zonen der zweiten Sklavenwirtschaft prägend waren für die im Entstehen begriffene industrielle Arbeitsteilung. Die aus dieser Perspektive vorgenommene Analyse der Zuckerproduktion in Jamaika, Guayana und Kuba offenbart die raumzeitliche Unterschiedlichkeit scheinbar ähnlicher historisch-geografischer Komplexe. Die vergleichende Untersuchung zeigt, wie weltwirtschaftliche Prozesse bestimmte lokalgeschichtliche Entwicklungen herbeiführen und solche Entwicklungen wiederum die Weltwirtschaft als Ganze strukturieren. Dieser Ansatz verortet die Krise der Sklavenwirtschaft im 19. Jahrhundert, in den unterschiedlichen Reaktionen auf Prozesse weltweiter Kapitalakkumulation, und nicht etwa in der Unvereinbarkeit von sklavenbasierter Produktion mit Industrialisierung und offenen, von Konkurrenz geprägten Märkten. In einem allgemeineren Sinn wird dadurch auf die Kontinuität von Formen der Zwangsarbeit innerhalb der historischen Entwicklung der kapitalistischen Weltwirtschaft verwiesen. Es wird außerdem darauf aufmerksam gemacht, wie Prozesse kapitalistischer Entwicklung auf Weltebene Formen sozio-ökonomischer Ausdifferenzierung und Hierarchisierung hervorbringen. Übersetzung: Max Henniger Dale Tomich. La segunda esclavitud y el capitalismo mundial: Perspectivas para una investigación histórica. El concepto de la segunda esclavitud supone un reinterpretación radical de la relación existente entre esclavitud y capitalismo llamando la atención en la emergencia de extensas nuevas áreas de producción esclavista de mercancías en el sur de los Estados Unidos, en Cuba y en Brasil como parte del proceso de industrialización a lo largo del siglo XIX y de la expansión económica mundial. En este artículo se examina el marco conceptual y los procedimientos metodológicos que conducen a esta interpretación. En él se reformula el concepto de economía mundo capitalista poniendo énfasis en la mutual formación e interrelación histórica de la relaciones globales-locales. Esta concepción abierta de la economía-mundo nos permite una especificación espacio-temporal de las regiones de la segunda esclavitud. De esta forma, resulta posible tanto distinguir las nuevas zonas donde se da la segunda esclavitud de aquellas zonas de producción esclavista previas en la economía-mundo, como establecer las formas en que participan en la configuración de la emergente división mundial del trabajo industrial. Desde esta perspectiva, el análisis de la producción azucarera en Jamaica, Guyana y Cuba revela algunas diferencias espacio-temporales entre lo que de otra manera se tomaría como complejos histórico-geográficos aparentemente semejantes. Esta comparación demuestra cómo los procesos de la economía-mundo producen historias locales particulares y cómo dichas historias estructuran la economía-mundo como un todo. Este enfoque ubica la crisis de la esclavitud durante el siglo XIX en la respuesta diferenciada a los procesos de acumulación mundial, en vez de incidir en la incompatibilidad de la producción esclavista con la industrialización y los mercados abiertos y competitivos. De forma más general, llama la atención sobre la continuidad de las formas de trabajo forzoso en el desarrollo histórico de la economía-mundo capitalista y sobre las formas en que los procesos de desarrollo capitalista producen una diferenciación y una jerarquía socioeconómica a escala mundial. Traducción: Vicent Sanz Rozalén